Evolución del estado nutricional en niños menores de cinco años hospitalizados en el servicio de medicina pediátrica del Hospital Belén de Trujillo - Moreno Reyna, Diana Adalid (2016)
The population of children under five years is the most vulnerable to malnutrition in hospitals group. PROBLEM: What is the evolution of the nutritional status of children under five hospitalized in the Pediatric Hospital Medicine Bethlehem Trujillo in the period December 2013-July 2014? OBJETIVE: To determine the evolution of the nutritional status of children under five patients hospitalized in the Pediatric Hospital Medicine Bethlehem Trujillo in the period December 2013-July 2014 through anthropometric parameters. MATERIALS AND METHODS: electronic measurement of weight and height balance with Infantometer or measuring rod. RESULTS: of 147 patients, 12.93% changed their nutritional status. This variation with time of hospitalization: a higher percentage less time is longer and maintains greater percentage of deterioration. Most nutritional variation was 1a - <3 years and in diagnostic low probability of impact on nutritional status (respiratory disease). CONCLUSIONS: Comparing the nutritional status of entry and exit was no difference, improved 6.8%, 87.08% and 6.12% remained worsened